2020
DOI: 10.1039/c9mh00835g
|View full text |Cite
|
Sign up to set email alerts
|

The structural fate of lipid nanoparticles in the extracellular matrix

Abstract: Hydrogels cause unilamellar liposomes to transform into aggregates of multilamellar structures through an osmotic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 77 publications
1
15
2
Order By: Relevance
“…For example, SAXS has been recently used to study the structural fate of lipid nanoparticles in the ECM. 74 We have also shown in previous work that in situ monitoring of the AuNPs transformation inside cells was enabled by SAXS. 12 This SAXS study was performed on three types of polymergrafted NPs: PMAA(7)-AuNPs, PMAA(11)-AuNPs, and PMAA(19)-AuNPs.…”
Section: ■ Results and Discussionsupporting
confidence: 57%
“…For example, SAXS has been recently used to study the structural fate of lipid nanoparticles in the ECM. 74 We have also shown in previous work that in situ monitoring of the AuNPs transformation inside cells was enabled by SAXS. 12 This SAXS study was performed on three types of polymergrafted NPs: PMAA(7)-AuNPs, PMAA(11)-AuNPs, and PMAA(19)-AuNPs.…”
Section: ■ Results and Discussionsupporting
confidence: 57%
“…This may be attributed to the inefficient release of liposomes decreasing the antitumor performance of BF211@Lipo. 42 Additionally, the uptake of BF211@Lipo was evaluated on normal Raw 264.7 macrophages and HepG2 tumor cells ( Figure S3B and C ). The results indicated that BF211@Lipo were more ingested by tumor cells, showing a certain cell selectivity, which would be beneficial to reduce phagocytosis and toxicity to normal cells, enhancing the specific antitumor therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Such functional supramolecular polymers feature properties beyond the classical role of DNA in biological systems, with applications in optoelectronic devices, drug delivery systems, and diagnostics to name a few. [20][21][22][23][24][25][26][27][28] However, vesicular morphologies are predominantly reported from lipid-DNA conjugates or DNA functionalized liposomes, [29][30][31][32][33][34] while the field apart from lipid-based DNA constructs remains largely unexplored. 35 In previous work, we demonstrated the self-assembly of phenanthrene-DNA conjugates into vesicular structures with light-harvesting features.…”
Section: Introductionmentioning
confidence: 99%